Aircraft survivability modeling, evaluation, and optimization for multi-UAV operational scenarios - Lunsford, Ian, author; Bradley, Thomas, advisor; Borky, John, committee member; Shahroudi, Kamran, committee member; Arabi, Mazdak, committee member (Colorado State University. Libraries, 2021)
The unmanned aerial vehicle (UAV) has become a prominent aircraft design throughout aerospace applications including commercial, civilian, and military. A UAV is preferred in some missions and applications due to its unique abilities compared to manned aircraft. This dissertation aims to define an improved understanding of the concepts and modeling of aircraft survivability, as applied to UAVs. Traditionally, survivability as a field has defined and considered survivability primarily in the context of manned aircraft, and single aircraft. With UAV's increasing importance in multi-UAV operational scenarios, it has become increasingly important to understand aircraft survivability for singles and groups of UAVs. This research effort has been structured into three research questions defining contributions in survivability modeling, validation, and UAV aircraft design. Research Question 1 seeks to demonstrate the feasibility of a parametric model of UAV survivability. The result is a UAV survivability model and simulation which illustrates key tradeoffs within UAV survivability. The effects on survivability on UAV design characteristics (speed, wing area, drag and lift coefficients) is quantified specific to the detailed lethal envelope simulation method. Research Question 2 aims to verify and validate the UAV survivability simulation, providing evidence of the predictive capability of the survivability simulation results. Evidence is presented for verification and validation through comparison to previous modeling efforts, through solicitation of expert opinion, and through parameter variability and sensitivity analysis. Lastly, Research Question 3 seeks to apply the simulation results to multi-UAV tactical evaluation and single aircraft design. The results illustrate the level of improvement that can be realized through UAV design including armoring (a 25% survivability improvement through 1000kg of armoring), speed increases (a 100 mph increase in cruise speed realizes a 14% decrease in killability), and other relevant design variables. Results also demonstrate that multi-UAV tactics can improve the survivability of UAVs in combat. Loyal wingman tactics are simulated to increase the survivability of a C-130J (equivalent UAV) from 19.8% to 40.0%. Other single UAV tactics such as fuel dumping, afterburners are evaluated under the same framework for their relative effectiveness. This dissertation answers the described research questions by presenting an aircraft survivability evaluation approach that relates survivability with modern UAV applications, emerging threats, multi-UAV tactics, and UAV design. Aircraft survivability encounters with modern UAV countermeasures are considered and simulated. UAV metrics of performance are modeled and simulated to describe aircraft design parameters sensitive to improving aircraft survivability. By evaluating aircraft survivability with a modern multi-UAV tactical perspective, this study seeks to provide the UAV designer with more complete vision of survivability-derived design criteria.
Keywords: aircraft survivability; Monte Carlo; UAV; modeling and simulation; aerospace; systems engineering